Effectiveness of Donggala Police Socialization in Preventing the Spread of Covid-19 - Wafika Nur Romadhani (Journal of Public Health and Pharmacy)
This research aims to determine the effectiveness of the Donggala Police's socialization in preventing the spread of Covid-19 in Banawa sub-district.